2018
DOI: 10.1002/ppsc.201800414
|View full text |Cite
|
Sign up to set email alerts
|

Facile Functionalization of Gold Nanoparticles with PLGA Polymer Brushes and Efficient Encapsulation into PLGA Nanoparticles: Toward Spatially Precise Bioimaging of Polymeric Nanoparticles

Abstract: Nanocarriers prepared from poly(lactide‐co‐glycolide) (PLGA) have broad biomedical applications. Understanding their cellular uptake and distribution requires appropriate visualization in complex biological compartments with high spatial resolution, which cannot be offered by traditional imaging techniques based on fluorescent or radioactive probes. Herein, the encapsulation of gold nanoparticles (GNPs) into PLGA nanoparticles is proposed, which should allow precise spatial visualization in cells using electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…As prepared GSH-AuNCs are extremely hydrophilic and thus it is clear that surface hydrophobication of these nanoclusters is required for their efficient encapsulation into PLGA nanoparticles. Recently, we reported the necessity of hydrophobication of larger gold nanoparticles (15 nm) to ensure efficient encapsulation into PLGA nanocarriers 23 . Accordingly, we aimed first to develop a simple and efficient protocol to render these peptide-capped nanoclusters hydrophobic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As prepared GSH-AuNCs are extremely hydrophilic and thus it is clear that surface hydrophobication of these nanoclusters is required for their efficient encapsulation into PLGA nanoparticles. Recently, we reported the necessity of hydrophobication of larger gold nanoparticles (15 nm) to ensure efficient encapsulation into PLGA nanocarriers 23 . Accordingly, we aimed first to develop a simple and efficient protocol to render these peptide-capped nanoclusters hydrophobic.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of gold in samples was measured with ICP-MS according to previous report 23 . For the sample preparation, 150 µL of freshly prepared aqua regia (HCl:HNO 3 = 3:1) was added to 50 µL of the sample, and the mixture were kept in an auto-shaker for overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polylactic acid-glycolic acid (PLGA) is a biodegradable polymer compound, which is polymerized by lactic acid and glycolic acid. It has been widely used as tissue engineering materials, implant materials, or drug carriers [24][25][26][27]. The use of PLGA can make up for the structural and performance defects of most materials to increase the penetration rate of existing materials.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported accumulation at the tumor site after intravenous injection and increased local temperature at the tumor up to 44 °C, resulting in inhibited tumor growth. Magnetic nanoparticles have also been utilized by several groups for cancer detection and ablation through tandem MRI and hyperthermic treatment after localization at the tumor site [292][293][294][295][296][297][298]. Today these properties are used synergistically with therapeutics, as discussed here.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%